Effects of Statins on Serum n-3 to n-6 Polyunsaturated Fatty Acid Ratios in Patients With Coronary Artery Disease. (July 2013) - Nozue, Tsuyoshi; Yamamoto, Shingo; Tohyama, Shinichi; Fukui, Kazuki; Umezawa, Shigeo; Onishi, Yuko; Kunishima, Tomoyuki; Sato, Akira; Nozato, Toshihiro; Miyake, Shogo; Takeyama, Youichi; Morino, Yoshihiro; et al.
Background: A low n-3 to n-6 polyunsaturated fatty acids (PUFAs) ratio is reported to be associated with cardiovascular events. However, the effects of statins on this ratio have not been fully examined. Methods: A total of 101 patients with coronary artery disease, who were not receiving lipid-lowering therapy were randomly assigned to receive either 4 mg/day of pitavastatin or 20 mg/day of pravastatin. Serum PUFA levels were measured at baseline and 8 months after treatment with statins. Results: Pitavastatin was used to treat 51 patients and the remaining 50 patients were treated using pravastatin. A significant positive correlation was observed between the percent change in low-density lipoprotein cholesterol and that in dihomogamma-linolenic acid ( r = .376, P = .007), arachidonic acid (AA; r = .316, P = .02), eicosapentaenoic acid (EPA; r = .408, P = .003), or docosahexaenoic acid (DHA; r = .270, P = .056) in the pitavastatin group. However, these correlations were not observed in the pravastatin group. The DHA/AA ratio decreased significantly in the pitavastatin group only (from 0.96 to 0.83, P = .0002) and the DHA/AA ratio was significantly lower in the pitavastatin group at 8 months (0.83 vs 0.96, P = .03). The EPA/AA ratio did not show significant changes in either group. Conclusions: Pitavastatin decreased the serum DHA/AA ratio, whereas pravastatin had no effect on this ratio. Neither pitavastatin nor pravastatin had an effect on the serum EPA/AA ratio in patients with coronary artery disease.